Geogrid Reinforcement of Asphalt Pavements - Adam Zofka; Maciej Maliszewski; Ewa Zofka; Miglė Paliukaitė; Laura Žalimienė (The Baltic Journal of Road and Bridge Engineering, 2017)
Geogrid materials applied within asphalt layers defer or prevent the occurrence of reflective cracking. The contribution of this work significantly adds to extending pavement serviceability and improving benefit/cost analysis. Since 1970s many studies have demonstrated the benefits of geogrid reinforcement in asphalt pavements, but this knowledge did not translate to their extensive usage in the actual construction practice. Among potential reasons are higher initial costs, lack of in-depth understanding of working mechanism within adjacent asphalt layers and lack of commonly standard design procedures. This paper presents a recent study, which investigated the effect of geogrid reinforcement on asphalt mixture specimens. Two types of laboratory experiments were conducted, namely monotonic (strength and fracture) testing and cyclic (fatigue and modulus) testing. The results demonstrated a significant strengthening contribution of geogrid, which was observed regarding fracture energy results and terminal deflections in the fatigue testing. This paper also presents a short example connecting pavement deflections with the allowable axle loading (also known as fatigue life) to demonstrate the practical implications of geogrid reinforcement. The undertaken analysis shows the reduction of pavement deflections due to the geogrid application, which potentially leads to a significant extension of pavement fatigue life. Paper concludes with several recommendations for further work in the area of geogrid reinforcement.